Empowering The Drupadi Cluster In The Digital Era Parenting Program In Semarang Public Elementary Schools - Muslikah, Muslikah; Kesuma, Rossi Galih; Kurnianto, Bagas; Nazhifa, Qanita Najla; Wulansari, Khikmah Eny (Universitas Negeri Semarang, 2024)
The VUCA (Volatility, Uncertainty, Complexity, and ambiguity) phenomenon currently being discussed among the wider community also impacts parenting management, disrupting parenting treatment. Learners are faced with rapid technological developments that require a digital-based parenting approach. On the other hand, teachers and parents need knowledge about parenting program education that is linear with advances in science and technology. The purpose of this service is to increase the understanding of parents and guardians of students about parenting in the digital era and to assist with parenting programs that the Drupadi Cluster Teacher Community has determined. The results of initial interviews with several teachers at schools covered by Gugus partners show there are problems faced by Gugus Drupadi partners, which include the high level of dependence of students on gadgets, as well as the lack of parental attention to the learning process of students at home, becoming a severe challenge in the character building and development of students in elementary schools. Based on these problems, the solution offered is to educate parents as the first madrasah for students about the fulfillment of intact parenting in the digital era, which is accelerated in the Empowerment of Gugus Drupadi in the Parenting Program in Public Elementary Schools in Semarang City. The service team has two roles. The first is to facilitate the stimulation of the parents of the Drupadi Cluster. Facilitators have an essential role in educating, motivating, and implementing digitally charged parenting treatments. The second role is as a companion for the programs determined by the Teacher Community in Gugus Drupadi.